Equity in access and graduation in higher education: Reflections from the Southern Cone - García de Fanelli, Ana María; Adrogué, Cecilia (Education Policy Analysis Archives, 2019)
The analysis of the equity of mass higher education systems in Latin America indicates how important it is to ensure that young people in the lower income sectors can study and obtain a degree. In this sense, the Southern Cone region constitutes an interesting case study to analyze the results in terms of access and graduation through the implementation of selective admissions policies, institutional diversification and privatization (Chile); or free and unrestricted access in the public sector in a diversified institutional environment (Argentina) or low institutional diversification (Uruguay). The comparative analysis of these countries reveals the relevance of analyzing not only the public and institutional policies of access and sources of funding and the evolution of the indicators regarding access and graduation in each case, but also of studying what occurs in terms of institutional differentiation, its association with social stratification and prestige allocation. Thus, the indicators show improvements over time, but in institutional contexts that maintain certain patterns of social inequality.